Case Report: Myocarditis Associated With COVID-19 mRNA Vaccination Following Myocarditis Associated With Campylobacter Jejuni - Kojima, Nobuko; Tada, Hayato; Okada, Hirofumi; Yoshida, Shohei; Sakata, Kenji; Usui, Soichiro; Ikeda, Hiroko; Okajima, Masaki; Kawashiri, Masa-aki; Takamura, Masayuki (Frontiers in Cardiovascular Medicine, 2022)
We herein present our experience with a case involving a 17-year-old Japanese boy suffering from acute myocarditis after his second coronavirus disease-2019 (COVID-19) messenger RNA (mRNA) vaccine shot. The patients had a history of myocarditis associated with Campylobacter jejuni 3 years prior. This has been the first-ever documented case of myocarditis associated with COVID-19 mRNA vaccination in a patient with a history of myocarditis. We present a series of images and blood biomarkers for different types of myocarditis that developed in this single patient.